2020
DOI: 10.21203/rs.3.rs-135680/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pyrroloquinoline Quinone Regulates the Redox Status in Vitro and Vivo of Weaned Pigs via the Nrf2/HO-1 Pathway

Abstract: BackgroundOxidative stress is a main cause of piglet gut damage and diarrhea. Pyrroloquinoline quinone (PQQ), is a novel redox cofactor with antioxidant properties. However, the effect and mechanism that PQQ supplementation decreases oxidative injury in weaned pigs is not understood. Therefore, the aim of this study is to confirm the effect of PQQ on regulating redox status in weaned pigs and the mechanism for antioxidant function by porcine intestinal epithelial cell line (IPEC-J2) challenged with H2O2.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…13 Besides, PQQ improved the antioxidant status and decreased the concentration of inflammatory factors in the intestines of weaned pigs. 14 Previously, we demonstrated that dietary supplementation with PQQ improved intestinal health and the growth performance of weaned pigs. 15,16 Inflammatory injury of the jejunal mucosa can be alleviated with dietary PQQ by inhibiting nuclear factor kappa-B (NF-κB) pathways in weaned pigs challenged with E. coli K88.…”
Section: Introductionmentioning
confidence: 98%
“…13 Besides, PQQ improved the antioxidant status and decreased the concentration of inflammatory factors in the intestines of weaned pigs. 14 Previously, we demonstrated that dietary supplementation with PQQ improved intestinal health and the growth performance of weaned pigs. 15,16 Inflammatory injury of the jejunal mucosa can be alleviated with dietary PQQ by inhibiting nuclear factor kappa-B (NF-κB) pathways in weaned pigs challenged with E. coli K88.…”
Section: Introductionmentioning
confidence: 98%
“…10 PQQ also possesses the ability to influence the cellular redox state, which plays an important role in regulating cell viability. 11,12 PQQ scavenges reactive oxygen species (ROS) to attenuate oxidative stress and stimulates mitochondrial biogenesis, and its deficiency influences the normal energy metabolism and mitochondrial function. 13,14 Since mitochondria and redox state play a central role in cell apoptosis, 15 PQQ is proposed to be a therapeutic agent to reverse the neural damage that is closely linked to mitochondrial dysfunction after cerebral hemorrhage.…”
Section: Introductionmentioning
confidence: 99%